The administrative judge and the constitutional judge: Expanded jurisdiction and reciprocal influence in protecting individual rights — a comparative study - Al Maagbeh, Moh'd Mofadi Faleh; Alwaqfi, Alla Adnan Mustafa; Al Maaqbeh, Abdullah Mohammad Mofadi; Alayaydeh, Hamza Ali Suleiman; Aloudat, Basil Ammar Abdelfattah; Altaani, Muhanned Farhan Mohammad; Alhendi, Noor; Alrfoua, Amal Yousef; Altarawneh, Mohammad Meeush (Research Journal in Advanced Humanities, 2026)
This research examines the mutual influence between the administrative judge and the constitutional judge through a comparative analytical framework. It begins by exploring the role of the administrative judge in safeguarding individual rights and freedoms, highlighting key mechanisms that demonstrate the effectiveness of administrative judicial oversight—such as proportionality review and scrutiny of disciplinary measures. The study then addresses the French Priority Question of Constitutionality (QPC), often referred to as the mechanism for raising unconstitutionality, to illustrate how this procedure has expanded the administrative judge’s involvement in assessing the constitutionality of legislative provisions. The research subsequently turns to the constitutional judge’s role in protecting rights and freedoms, drawing particularly on the achievements of the French Constitutional Council— beginning with its landmark 1971 decision on freedom of association, which conferred constitutional value on the Preamble to the 1958 Constitution. Central to the significance of the Constitutional Council’s jurisprudence is the binding force of its decisions, which automatically impose obligations on both the judiciary and the administration. Finally, the study analyzes the positive reciprocal influence between administrative and constitutional judges. It demonstrates that the administrative judge, through participation in constitutional review mechanisms, has in some respects evolved into a “miniature constitutional council.” The research also highlights the view of jurist Bernard Stirn, who argues that while the administrative judge remains careful not to encroach upon the Constitutional Council’s authority, he nevertheless exercises strong and impactful control that can indirectly shape constitutional reasoning. Although the dynamics of mutual influence may fluctuate over time, the overarching relationship is characterized by harmony and cooperation, which ultimately enhances the protection of rights within the legal system.